Апазіцыя «сваё - чужое» у ранняй лірыцы Янкі Купалы: нацыятворчы аспект - Вабішчэвіч, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The categories «own» and «alien» have become for Janka Kupala the effective instrument of nation-building activity in the beginning of his creative work (1905–1908). The use of this binary opposition played the role of the starting point for the development of the extensive art programme directed to Belarusian national awakening. The antinomy «own – alien» permitted the poet to employ the internal self-defended potential of Belarusian nation and activate the self-knowledge and identification mechanisms, which are the necessary condition for the successfulness of Belarusian nation-building process.